Microbial degradation of polylactic acid bioplastic - Noor Dina Muhd Noor (2024)
In modern urban society, plastic has become a major component in many applications. Despite their usefulness, plastics are known for their alarming resistance to biodegradation and therefore pose a huge burden on the environment. The surge in plastic waste has led to the development of biodegradable plastics. Biodegradable plastics are perceived to be one of the sustainable ways to reduce plastic wastes. Among the biodegradable plastics, polylactic acid (PLA), a bio-based plastic, has been widely used for diverse applications. PLA however, is known to be less susceptible to biodegradation and requires longer time to degrade in the natural environment compared to other aliphatic polyesters. Therefore, identification of PLA-degraders is the current focus of research. Potential PLA-degraders have been isolated from various sources, but the number is still limited. Considering temperature as one of the important factors in biodegradation, in this review, we categorize PLA degraders into three groups; thermophilic, mesophilic and psychrophilic, and discuss their relevance to PLA biodegradation. Enzymes associated with PLA degradation are described according to their temperature preference. One of the current limitations is the structural insights into the catalytic mechanism. Discovery of more PLA-degraders and understanding of the mechanism could aid in designing strategies to accelerate the biodegradation process.